A new distinctive lineage of Helix (Gastropoda, Stylommatophora, Helicidae), with a guide to Helix species from mainland Greece - Ondřej Korábek; Petr Dolejš; Radovan Coufal; Lucie Juřičková; Kateřina Kubíková; Bernhard Hausdorf (ZooKeys)
Greece is home to numerous endemic land snail species, sometimes with highly restricted distributions. Several species of Helix, representing all three subgenera, live there. Although the genus was taxonomically revised in 2014, there remained some open questions and the distribution ranges of individual species are still incompletely known. The discovery of a new, narrowly endemic subspecies, Helix pelagonesica thembones Korábek, Juřičková & Hausdorf, subsp. nov., is reported from the hills bordering the Thessalian Plain in the west. It was previously confused with Helix schlaeflii, but it was found that H. schlaeflii does not occur as far east as previously thought. Notably, the isolated populations from the tip of the Sithonia peninsula (Chalkidiki) that had previously been identified as H. schlaeflii also turned out to be related to H. pelagonesica. Although a divergent mitochondrial lineage was found there, morphological differences limited only to a different shell shape and lack of geographic separation led us to classify these populations as a form of H. pelagonesica pelagonesica. In addition, Helix straminea is reported from Greece for the first time, with a population located near Kalambaka. All the Helix species from mainland Greece are illustrated and accompanied by descriptions to facilitate their recognition and maps of their distribution are provided.